Five cardiopathies, one heart - Silva C, Gastón; Nasser, Chadi; Yajure M, Isaubett (Gaceta Médica de Caracas, 2021)
This clinical case reports a patient diagnosed with a partial 1- Cor Triatriatum Sinister associated with 2-severe calcified mitral stenosis and accessory subvalvular mitral tissue, 3- membranous subvalvular aortic stenosis, 4- severe aortic valve regurgitation, and 5- patent conduct arteriosus (PCA), with mild depressed ejection fraction and moderate pulmonary hypertension who underwent surgery for successful membrane resection and corresponding mitro-aortic valve replacement, in addition to closing intracardiac of the patent artery duct. Cinco cardiopatías, un corazón El presente caso clínico trata sobre un paciente con diagnóstico de 1- Cor Triatriatum Sinister parcial asociado a 2. Estenosis mitral severa calcificada y tejido subvalvular mitral accesorio, 3. Estenosis subvalvular aórtica membranosa, 4. Insuficiencia valvular aórtica severa y 5. Persistencia del conducto arterioso (PCA), con fracción de eyección deprimida leve e hipertensión pulmonar moderada. Se le realizó de manera exitosa resección de las membranas, además del cierre intracardíaco del conducto arterioso y reemplazo valvular mitro-aórtico.